La muerte de un burócrata - Gutiérrez Alea, Tomás, 1928-1996; Cueto, Alfredo L. del; Suárez, Ramón F.; Vud, Salvador (Instituto Cubano del Arte e Industrias Cinematográficos, 1996)
Sarcastic and humorous portrayal of Cuban bureaucracy as seen in the story of a man's mounting frustration with his fruitless attempts to procure the pension of a recently-deceased uncle.